A recyclable anhydrous cotton dyeing technology with low energy consumption and excellent dyeing effects by mixing supercritical carbon dioxide, ethanol, and dimethyl sulfoxide. (20th September 2022) - Zhao, Hongjuan; Wang, Hongxin; Wang, Mingyue; Bai, Puzhou; Tan, Lichuan; Xiong, Xiaoqing; Zheng, Laijiu
Abstract: Traditional cotton water dyeing has a considerable ecological impact because of the use of water, but the available anhydrous cotton dyeing technologies cannot balance low recyclable energy consumption and excellent dyeing effects. In this study, a recyclable anhydrous cotton dyeing technology was designed and implemented by mixing supercritical carbon dioxide, dimethyl sulfoxide, and ethanol for the first time. Compared to the existing anhydrous cotton dyeing technologies, the novel technology could simultaneously obtain low recyclable energy consumption and excellent dyeing effects, such as dye penetration, washing and crocking fastness, levelness, color depth control and color matching. The dye fixations of reactive dyes in the novel technology are 5.1%–26.4% higher than those in traditional water dyeing. Meanwhile, the energy consumption of the novel technology is only 70% of that of traditional water dyeing, and the comprehensive cost of materials and energy of the novel technology is only 56% of that of traditional water dyeing. It is a new green option with low energy consumption for cotton dyeing. Graphical abstract: Image 1 Highlights: No water involves in SC-CO2 /EtOH/DMSO multi-medium dyeing. All dyeing media of SC-CO2 /EtOH/DMSO multi-medium dyeing are recyclable. SC-CO2 /EtOH/DMSO multi-medium dyeing is a low-energy process. SC-CO2 /EtOH/DMSO multi-medium dyeing has excellent dyeing effects.